Case report and literature review: removal of a mercury thermometer from the abdomen of a 16-year-old boy under laparoscopy - Hou, Runjie; Wang, Jijun; Guo, Jing; Du, Mingyue; Dong, Zhenyu; Song, Xiaobiao (Frontiers in Surgery, 2024)
IntroductionThe incidence of foreign bodies within the human body is uncommon, with thermometers representing an exceptionally rare subset of such cases. The management of these cases is particularly challenging due to the fragility of mercury thermometers and the toxic nature of their contents.Case descriptionA 16-year-old male adolescent presented with a three-month history of persistent, dull pain localized to the right inguinal region. Diagnostic imaging, including an abdominal upright x-ray and CT scans, revealed the presence of an intra-abdominal foreign body, specifically a thermometer. The diagnosis was subsequently confirmed intraoperatively through laparoscopic exploration. The foreign body was successfully extracted via laparoscopic intervention. The patient's postoperative course was uneventful, leading to discharge on the second day following the procedure. A one-month follow-up examination revealed no complications.ConclusionA comprehensive literature review was conducted, focusing on cases involving thermometers as foreign bodies. The diagnostic and treatment experiences from the present case were integrated into this analysis. Based on these findings, a summary of diagnostic and treatment strategies for thermometer-related foreign body incidents has been formulated. It is recommended that an abdominal upright x-ray examination be employed as the primary diagnostic modality. The integrity and location of the thermometer, along with the presence of associated complications, should be considered as crucial factors in determining the most appropriate treatment approach. Furthermore, it is imperative to address the psychological and mental health aspects of these cases, particularly in adolescent patients.